Pengaruh Koneksi Politik terhadap Manajemen Laba dengan Moderasi Keahlian Komite Audit - Rini Adriani Auliana (Program Studi Akuntansi FPEB UPI, 2023)
Abstract. This research aims to prove the effect of political connections on earnings management and prove audit committee’s expertise in weakening the effect of political connections on earnings management. The population is manufacturing companies listed on the Indonesia Stock Exchange during 2017-2020. Sample selection using purposive sampling technique by certain criteria. The number of sample is 102 manufacturing firms with 408 observations during four observation years. The hypotheses were tested using two anaylsis, that is multiple regression analysis and moderated regression analysis. The results showcased that political connection has no effect on earnings management and audit committee’s expertise as a moderating variabel cannot weakening the effect of political connections on earnings management.Keywords. Earnings Management; Political Connection; Audit Committee Expertise